Analisis Administratif, Farmasetis, dan Klinis pada Resep Dokter di Apotek A Kota Surakarta - Firra Lurenza Pratiwi; Reni Ariastuti; Risma Sakti Pambudi (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Prescription screening is a pharmaceutical service in pharmacies. A prescription is a doctor's written request to the pharmacist to provide drugs for the patient on the prescription. The study aims to determine the suitability of drug prescribing from administrative, pharmaceutical, and clinical aspects at pharmacy A in Surakarta during January - December 2021. The sampling method is retrospective, namely research based on data from pharmacy prescription archives. Data analysis is shown the percentage of the completeness of the recipe components in January - December 2021 with 100 samples. Data analysis used Microsoft Excel 2013 by entering the data obtained. The results of administrative analysis prescriptions did not meet the requirements in the doctor's SIP (23%), doctor's name (4%), doctor's initials (2%), patient's weight (95%), address (7%), age (4 %), while the aspects fulfilled (100%) the patient's name, gender, practice address and date of the prescription. The pharmaceutical analysis did not meet the requirements, namely the writing of the dosage strength (8%), while the name of the drug, dosage form, amount of drug, and directions meet the requirements (100%). Clinical analysis of drug dose adjustment (1%) and drug interactions (7%) with interactions are pharmacokinetic and pharmacodynamic interactions. The conclusion is there are still errors in prescribing (medication errors) in the administrative, pharmaceutical, and clinical aspects but most of the prescribing errors occur in the administrative aspects of the prescription.